Being Highly Skilled and a Refugee: Self-Perceptions of Non-European Physicians in Sweden. (19th March 2018) - Mozetič, Katarina
ABSTRACT: Both in popular imaginings as well as in migration scholarship, migrants are generally placed into different categories. We know, for instance, of refugees, family migrants, international students, and highly skilled migrants. This article seeks to document the narratives of people standing at the junction of the usually separated categories of "refugee" and "highly skilled migrant", and to account for the complex criss-crossings of their professional and refugee identities. The article is based on semi-structured interviews with non-European medical doctors who came to Sweden as refugees. In order to make sense of how these highly skilled refugees understand themselves, what they identify with, and what social locations they occupy in the destination country, the article employs Rogers Brubaker and Frederick Cooper's distinction between "identification and categorization" and "self-understanding and social location". These concepts have further been developed by Richard Jenkins's theory on social identity and Floya Anthias's work on translocational positionality. The article points to the processual nature of identity, which is always partly self-constructed and partly determined by external categorisations, and hence makes the case against the essentialisation of migrants' identities, be they "refugee" or "highly skilled migrant".